Antioxidant vitamin levels in term and preterm infants and their relation to maternal vitamin status - Baydas, G; Karatas, F; Gursu, MF; Bozkurt, HA; Ilhan, N; Yasar, A; Canatan, H (Elsevier Science Inc, 2002)
Background. Lipid peroxidation plays a vital role in the pathogenesis of many neonatal complications. Preterm babies are especially predisposed to lung diseases and retinopathy, probably due to a deficiency in their antioxidant systems. Vitamins E, A, and C are part of the natural antioxidant defense systems. We aimed to determine the levels of vitamins E, A, and C in maternal and cord blood plasma of term and preterm infants and to investigate the relationships between these levels. Methods. In the present study we determined vitamin E, A, and C levels in the Umbilical cord blood of term (n = 30) and preterm (n = 22) infants and their mothers by HPLC. Blood samples were taken during delivery. Results. Levels of lipid soluble antioxidant vitamin E and A in cord blood were lower than maternal values (p <0.01, p <0.05, respectively). Conversely. the level of water-soluble vitamin C was higher in cord blood than in maternal level (p <0.05). Significantly higher levels of vitamins E. A, and C were found in term babies as compared with those born preterm (p <0.05). Conclusions. There was a positive correlation between maternal and cord blood levels of vitamins E and A (r = 0.775 r = 0.725, respectively). In conclusion, preterm babies have fewer lipid-soluble antioxidant vitamins in their serum compared to term infants. Therefore, it is possible to postulate that preterm infants are more susceptible to oxidative stress. (C) 2002 IMSS. Published by Elsevier Science Inc.
Keywords: antioxidant vitamins; preterm infants; term infants